Perspectives on flexible learning towards the development of proposed quality assurance framework for HyFlex learning - Gloria, Daianne S.; Pelayo, Elmira Thrina C. (Intelektual Pustaka Media Utama, 2025)
Quality assurance is a significant part of achieving sustainable development goal 4 and has remained a challenge to higher education institutions (HEIs) worldwide. Thus, this paper aims to propose a quality assurance framework for hybrid-flexible (HyFlex learning) learning based on the perspectives of faculty and students. This study utilized a descriptive developmental mixed-method research design to dissect the richness and beauty of the data collected using the self-developed survey questionnaire and interview protocol guide. The findings revealed that both students and faculty preferred the utilization of flexible learning as their learning modality. Also, a significant difference when grouped according to UNESCO’s quality and learning indicators is also observed in the study. Accessibility and usability, learning assessment strategies, vision and institutional leadership, learning activities and learning interaction, instructional materials, social and student engagement, stakeholders’ support, course structure, learning outcomes and competencies, evaluation and feedback, social and student engagement, flexibility and adaptability of education, security and safety, and infrastructure, facilities, and equipment were the emergent themes which were utilized to craft the quality assurance framework. The proposed framework provides a transparent and reliable workflow for implementing, monitoring, and evaluating quality assurance of all HyFlex learning modalities in the university.